Caracterização fisio-farmacológica de dispositivos de liberação controlada para o estudo do sistema renina angiotensina. - Millen Cristina Moreira Barbosa (2008)
In this work, we evaluate the viability of using biodegradable polymers for thedevelopment of controlled release systems for Losartan. Two kinds of formulations inPLGA (Poly-lactide- glycolide acid) base for Losartan were tested in anesthetized Wistarrats instrumented to arterial pressure register and intravenous administration of peptides.Of those doses tested during the initial acute experiments, the 3,0 mg/kg Losartan dosepresented better efficiency in blocking the pressure response caused by 20 ng of Ang II.After that, we tested the capacity of Ang II pressure effect blocking by the formulationsPLGA/Losartan and CI/PLGA, 2, 6, 12, 24, 36 and 48 hours after its subcutaneousadministration. An accented Ang II pressure effect blockade was obtained in both theanimals treated with PLGA/Losartan and CI/PLGA, when compared to its respectivecontrols during the 48 treatment hours. However, in the animals treated with Losartanonly, we observed a significant 24 hours Ang II pressure effect blockade, whencompared with the PLGA control and a 36 hours Ang II pressure effect blockade whencompared with the PLGA and -CD controls. After these periods, the pressure responsesin the Losartan group begin to return to control conditions, as the responses obtained inthe groups PLGA/Losartan and CI/Losartan remained acutely reduced. When comparingthe Losartan and the PLGA/Losartan treated animals, we noticed that there were nosignificant differences between them during the 48 hours of treatment. The same wasobserved when comparing the Losartan and the CI/PLGA groups. The cardiac frequencydata obtained for each experimental group are in agreement with what was observed forthe mean arterial pressure during the 48 hours of treatment. The findings of the acuteexperiments indicate that the Losartan encapsulation in PLGA and its inclusion in -CD,nearly doubled the duration of its action time, from 24 hours to 48 hours. In chronicexperiments we tested the Ang II pressure effect blockade at the end of 8 and 21 days oftreatment with both suspension and controlled release device pellets formulations.However, these experiments do not provide significant results concerning the Ang IIpressure effect blockade. In in vitro experiments performed with our preparations, theobserved burst effect (release of 100% of drug in one hour of experiment) indicates thatthe totality of the Losartan was released in the approximated time of 1 hour, provokingthe increase of just 1 hour in its liberation. This resulted in an increment of 24 hours inthe antagonist effect duration. We found that the PLGA based Losartan controlledrelease system represents a gain of 24 hours in the duration of the antagonist effect of thedrug and its metabolite, however, not to apply to chronic blockade. This occurs becauseeven little alterations in the Losartan conversion ratio in EXP3174 can result inimportant changes in the level and duration of the Ang II blockade. Our data suggest thatthe use of polymers with lower burst effect for Losartan may allow the development ofcontrolled release device of Losartan of long duration